(untitled) (Hekima Review, 2024)
The fourth issue of Hekima Review comes out at a time when the Catholic Church in Kenya is celebrating the centenary of her evangelization: an occasion of joy, thanksgiving, and meditation for all. of us. For this celebration, the Kenya Catholic Bishops have written a pastoral letter on the "Centenary of the Evangelization of Kenya." They conclude by launching an appeal for creativity to make the year 1989-1990 a time of grace and interior renewal. It is in this spirit of creativity that the fourth issue of Hekima Review has been produced.